A Systematic Literature Review of Brand Switching Behavior - Pratama, Ferdian Tomy; Haryanto, Budhi (Cita Konsultindo Research Center, 2025)
The article uses a systematic review literature that aims to summarize some research on brand switching behavior. This artike employs the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) technique with the aid of UAKE's Watase program. Literature gathered throughout the previous ten years from 2014 to 2024 was analysed using the Watase UAKE program to obtain article extraction in the form of article information. The findings of the analysis suggest that 2023 is the year with the greatest relevant number of publications, with five articles published. An study published in 2019 by Information Technology & People and titled